2017
DOI: 10.1093/rheumatology/kex286
|View full text |Cite
|
Sign up to set email alerts
|

The British Society for Rheumatology guideline for the management of systemic lupus erythematosus in adults

Abstract: Need for the guidelineDespite some improvement in survival data over the last 40 years (2;13), lupus patients still die on average 25 years earlier than the mean for women and men in the UK ( 16). The disease can present with slowly or rapidly progressive active disease at any age and can be associated with the rapid accumulation of damage if not promptly diagnosed, appropriately treated and regularly monitored (2;8;14;19;20). An up to date comprehensive guideline to optimise these aspects of management and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
314
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 279 publications
(347 citation statements)
references
References 351 publications
1
314
1
12
Order By: Relevance
“…Antimalarials are strongly recommended in SLE to prevent flares and reduce the development of renal disease and chronic damage and for its steroid-sparing properties [2328]. However, this study showed that only 60.7% of SLE patients were receiving hydroxychloroquine at the time of the study.…”
Section: Discussionmentioning
confidence: 91%
“…Antimalarials are strongly recommended in SLE to prevent flares and reduce the development of renal disease and chronic damage and for its steroid-sparing properties [2328]. However, this study showed that only 60.7% of SLE patients were receiving hydroxychloroquine at the time of the study.…”
Section: Discussionmentioning
confidence: 91%
“…Lupus affects eight times as many women as men 37 and the cheapest effective treatment for lupus nephritis, cyclophosphamide, can impair fertility if the dose is not minimized and the ovaries are not protected 38 . This risk deters women from accepting treatment.…”
mentioning
confidence: 99%
“…The high rate of patients with musculoskeletal and skin involvement may be the reason for the relatively high proportion of patients with mild disease treated with RTX in our population (26%). This group, according to the guidelines of the British Society of Rheumatology , should not be treated with RTX. However, it should be noted that for patients with less severe disease, RTX was used in the context of reduced therapeutic options since in this population disease had previously failed to respond to a mean of ~3 immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were stratified into the following 4 groups according to disease severity: mild, moderate, severe, and drug sparing. The first 3 groups were defined according to the British Society of Rheumatology guidelines . The group “drug sparing” included patients with mild or moderate disease to whom RTX was administered with the aim of sparing an ongoing immunosuppressive agent or avoiding an alternative immunosuppressant that was contraindicated in the patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation